Nation Building in Newly Merged Districts of Erstwhile FATA, Pakistan: An Analysis - Sana Noor; Sadia Suleiman, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The study explores Pakistan's efforts to carry out nation building in former Federally Administered Tribal Areas (FATA), as well as the concept of merger towards nation building and the extent to which it has been successful. The article derives its analysis from the theoretical framework of postliberal peace building; however, the article debates the core postulate of this theory; foreign intervention. Pakistan's nation-building in former FATA represents a new set of knowledge originating from domestic bodies, in contrast to post-liberal foreign interventionist phenomena. The parameters of nation building in Former FATA range from military intervention to the empowerment of local civil administration, with the two key concepts being inclusiveness and the realization of collective interests. This article adopts a qualitative analysis based on the available literature.